Pragmatically on the sense of taste – a short treatise based on culinary art - Waluga, Marek; Jonderko, Krzysztof; Buschhaus, Magdalena (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
The sense of taste is essential for proper functioning of the organism. The authors describe, in an accessible way, the complex mechanisms of taste perception. The structure of particular taste receptors, variants of their activation, as well as physical and chemical factors modifying the sensation of taste, are presented. Exquisite culinary examples are given in order to facilitate the reader with the understanding of why, at the level of the cerebral cortex, a virtually infinite number of combinations of taste sensations can be perceived. The discourse is spiced up by reflections of the eminent philosopher of taste, J.A. Brillat-Savarin, who convinces us that food intake should be not only a physiological act, but also a refined pleasure.